2021
DOI: 10.1177/00220426211055433
|View full text |Cite
|
Sign up to set email alerts
|

Feigning Symptoms to Obtain Prescription Stimulants: A Vignette-Based Study on Its Conditions

Abstract: This vignette-based study examined the willingness to feign symptoms to obtain a prescription following an analysis on who might use prescription stimulants to enhance performance ( N = 3,468). It experimentally manipulated three factors: the social disapproval of prescription stimulant use for enhancement purposes, the physicians’ diagnostic efforts, and the medical condition (attention-deficit/hyperactivity disorder and narcolepsy); respondent characteristics of self-control, personal morality, and self-effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 137 publications
(207 reference statements)
0
5
0
Order By: Relevance
“…In narcolepsy, nonspecific symptoms, especially in cases without cataplexy, and high rates of comorbidities may lead to inappropriate treatment or unsupervised self-treatment along with a higher risk for substance abuse/dependence (Lazareck et al, 2012;Dunne et al, 2016;Ruoff et al, 2017). Further, there have been reports of the imitation of narcoleptic symptoms by illegal substances, especially cannabis, or the feigning of narcoleptic symptoms (or ADHD characteristics), to obtain stimulants for resale or personal misuse/abuse (Dzodzomenyo et al, 2015;Dunne et al, 2016;Fuermaier et al, 2021;van Veen et al, 2022). Therefore, incorrect diagnoses might also have contributed to the higher proportion of narcolepsy in our study.…”
Section: Narcolepsymentioning
confidence: 99%
See 1 more Smart Citation
“…In narcolepsy, nonspecific symptoms, especially in cases without cataplexy, and high rates of comorbidities may lead to inappropriate treatment or unsupervised self-treatment along with a higher risk for substance abuse/dependence (Lazareck et al, 2012;Dunne et al, 2016;Ruoff et al, 2017). Further, there have been reports of the imitation of narcoleptic symptoms by illegal substances, especially cannabis, or the feigning of narcoleptic symptoms (or ADHD characteristics), to obtain stimulants for resale or personal misuse/abuse (Dzodzomenyo et al, 2015;Dunne et al, 2016;Fuermaier et al, 2021;van Veen et al, 2022). Therefore, incorrect diagnoses might also have contributed to the higher proportion of narcolepsy in our study.…”
Section: Narcolepsymentioning
confidence: 99%
“…Most studies on MPH abuse or misuse so far have been limited to regional or national data, people with a known SUD or certain age groups, typically college students (Teter et al , 2006; Kaloyanides et al , 2007; Frauger et al , 2011, 2013; 2016; Cairns et al , 2016; Faraone et al , 2020; Fuermaier et al , 2021; van Veen et al , 2022). There are almost no studies addressing MPH abuse in narcolepsy (Auger et al , 2005; Mantyh et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate and improve the instructions and instruments, the survey materials underwent pretesting (N = 5) using the think-aloud technique and probing questions (Van Someren et al, 1994) and a further pretest under naturalistic conditions (N = 34). The results of these pretests demonstrated the materials were clear, understandable and suitable for the nationwide sample.…”
Section: Pretestingmentioning
confidence: 99%
“…It has been shown that these pharmaceuticals can also improve cognitive abilities (i.e., memory, attention) in healthy individuals (Battleday & Brem, 2015; Roberts et al., 2020). For many, these substances are readily available via friends, family, by feigning symptoms at a doctor's office or via the black market (Faraone et al., 2020; van Veen et al., 2022). One study found that one in five people in the United States aged 16 to 65 reported taking enhancement drugs in the past year (Maier et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, people with low or a lack of overcommitment are less likely to misuse drugs when effort is high. Thus, their work motivation may not be high enough to make them willing to take the risk of experiencing side effects or face the challenge of obtaining such drugs, e.g., by feigning symptoms at the doctor's or finding relatives or friends who may share their medication [52][53][54]. These findings also suggest that, in the absence of a main effect of work stress on the outcome (here prescription drug misuse), work stress may exert differential effects, i.e., the investigated type of drug misuse follows different patterns depending on the combination of the extrinsic and the intrinsic component of the model.…”
Section: Summary and Interpretationmentioning
confidence: 99%